A robust monolithic metal–organic framework with hierarchical porosity. Issue 93 (5th November 2018) - Vilela, Sérgio M. F.; Salcedo-Abraira, Pablo; Micheron, Loïc; Solla, Eugenio L.; Yot, Pascal G.; Horcajada, Patricia
Abstract : Mechanically robust centimetric single-piece MOF monoliths with hierarchical porosity. Abstract : Hierarchical porous UiO-66-NH2 cm-monolithic xero- and aero-gels with a controlled shape and mechanical robustness were successfully produced from ethanolic gels. Their remarkable controlled hierarchical porosity was effectively assessed using N2 sorption, Hg intrusion porosimetry and focused ion beam-scanning electron microscopy methods.